Alcohol improves cerebellar learning deficit in myoclonus–dystonia: A clinical and electrophysiological investigation. Issue 4 (25th September 2017) - Weissbach, Anne; Werner, Elisa; Bally, Julien F.; Tunc, Sinem; Löns, Sebastian; Timmann, Dagmar; Zeuner, Kirsten E.; Tadic, Vera; Brüggemann, Norbert; Lang, Anthony; Klein, Christine; Münchau, Alexander; et al.
Abstract : Objective: To characterize neurophysiological subcortical abnormalities in myoclonus–dystonia and their modulation by alcohol administration. Methods: Cerebellar associative learning and basal ganglia–brainstem interaction were investigated in 17 myoclonus–dystonia patients with epsilon‐sarcoglycan ( SGCE ) gene mutation and 21 age‐ and sex‐matched healthy controls by means of classical eyeblink conditioning and blink reflex recovery cycle before and after alcohol intake resulting in a breath alcohol concentration of 0.08% (0.8g/l). The alcohol responsiveness of clinical symptoms was evaluated by 3 blinded raters with a standardized video protocol and clinical rating scales including the Unified Myoclonus Rating Scale and the Burke–Fahn–Marsden Dystonia Rating Scale. Results: Patients showed a significantly reduced number of conditioned eyeblink responses before alcohol administration compared to controls. Whereas the conditioning response rate decreased under alcohol intake in controls, it increased in patients (analysis of variance: alcohol state × group, p = 0.004). Blink reflex recovery cycle before and after alcohol intake did not differ between groups. Myoclonus improved significantly after alcohol intake ( p = 0.016). The severity of action myoclonus at baseline correlated negatively with the conditioning response in classical eyeblink conditioning in patients. Interpretation: The combination of findings of reduced baseline acquisition of conditioned eyeblink responses and normal blink reflex recovery cycle in patients who improved significantly with alcohol intake suggests a crucial role of cerebellar networks in the generation of symptoms in these patients. Ann Neurol 2017;82:543–553